Hubungan Kualitas Hidup dengan Gejala Depresi pada Pasien Artritis Reumatoid di RSUP Dr. M. Djamil Padang - Gina Matahati; Siti Nurhajjah; Arina Widya Murni (Pusat Riset dan Inovasi Nasional, 2025)
Rheumatoid arthritis (RA), as an autoimmune disease with a chronic inflammatory nature, can decrease quality of life, with depression in RA patients being one of the factors influencing the determination of quality of life. The purpose of this study was to determine the relationship between depression and the quality of life of RA patients at RSUP Dr. M. Djamil Padang. The type of research used is analytical case-control study. There were 60 samples consisting of 20 people with depressive symptoms in the case group and 40 people without depressive symptoms in the control group. The data analysis used was the Chi-Square correlation test. The results of this study showed female respondents, late adult age, and duration of illness less than five years were characteristics of most of the respondents of this study. Analysis with the Chi-Square test showed an association (p<0.05) between the quality of life of the emotion domain (p=0.000) and depressive symptoms in RA patients. Meanwhile, there was no association (p>0.05) between the quality of life of patients in the domains of physical function (p=1.000), physical role (p=0.208), pain (p=0.151), general health (p=0.308), social function (p=0.195), vitality (p=0.389), and mental health (p=0.255) with depressive symptoms in RA patients. To sum up, there is a correlation between depression and the emotion domain of QoL of RA patients but there is no correlation between depression and the physical function, physical role, pain, general health, social function, vitality, and mental health domain of QoL of RA patients.